ECLECTIC ARCHITECTURE ON MASJID PUSDAI BUILDING IN BANDUNG - Tamara Florenza ; Bachtiar Fauzy (Riset Arsitektur (RISA), 2018)
Abstract- Eclectic architecture is a product of globalization in which architectural styles from different places and time intertwine each other. The development of eclectic architecture in Indonesia tends to follow the trend, neglecting the local value. A study towards eclectic architecture is necessary to raise society’s concern towards the identification of foreign and local architectural style. Masjid PUSDAI Bandung is selected as a research object to represent these issues above, in which the architectural style of Spain, Indian, and Javanese mosque intertwined each other. The research’s purpose towards the research object as a representation of eclectic architecture is to define the meaning of eclectic architecture in Masjid PUSDAI as well as to understand the form of eclecticism in Masjid PUSDAI. The eclectic architecture form will be analyzed towards the mixture of Indian, Spain, and Javanese mosque architecture style.Literature study as a theoretical base consist of the main theories such as the theory of eclectic architecture and theory of form and technic, as well as the supporting theories such as the architecture of Spain, Indian, and Javanese mosque. A comparative-qualitative approach is used as research method. This method compares the documentation from building observation with the literature theories for a further analysis.Through this research it can be concluded that the eclectic architecture form of Masjid PUSDAI Bandung is seen through mixture of two to three architecture style among its elements, thus forming a new architecture style. However, the intertwinement of architecture style doesn’t show on several elements. Some of them show an identical form which is used in Indian, Spain, and Javanese mosque.This research is expected to educate readers, architecture students, and experts in academic fileds, about how to execute the eclectic architecture design in public facilities, especially on mosques in Indonesia. Keywords: eclectic, architecture, mosque